Association of frailty with clinical outcomes in myelofibrosis: a retrospective cohort study. (15th June 2021) - Bankar, Aniket; Alibhai, Shabbir; Smith, Elliot; Yang, Dongyang; Malik, Sarah; Cheung, Verna; Siddiq, Nancy; Claudio, Jaime; Arruda, Andrea; Tsui, Hubert; Capo‐Chichi, Jose‐Mario; Kennedy, James A.; et al.
Summary: There is limited understanding of the impact of frailty on clinical outcomes in patients with myelofibrosis (MF). In this retrospective cohort study on 439 chronic phase MF patients [mean age: 68·7 ± 12 years; median follow‐up: 3·4 years (IQR 0·4–8·6)] from 2004 till 2018, we used a 35‐variable frailty index (FI) to categorise patient's frailty status as fit (FI < 0·2, reference), prefrail (FI 0·2–0·29) or frail (FI ≥ 0·3). The association of frailty with overall survival (OS) and cumulative JAK inhibitor (JAKi) therapy failure was measured using hazard ratio (HR, 95% CI). In multivariable analysis, prefrail (HR 1·7, 1·1–2·5) and frail patients (HR 2·9, 1·6–5·5), those with higher DIPSS score (HR 2·5, 1·6–3·9) and transfusion dependency (HR 1·9, 1·3–2·9) had shorter OS. In a subset analysis of patients on JAKi treatment ( n = 222), frail patients (HR 2·5, 1·1–5·7), patients with higher DIPSS score (HR 1·7, 1·0–3·1) and transfusion dependence (HR 1·7, 1·1–2·7) had higher cumulative incidence of JAKi failure. Age, comorbidities, ECOG performance status, and MPN driver mutations did not impact outcomes. Thus, higher frailty scores are associated with worse OS and increased JAKi failure in MF, and is a superior indicator of fitness in comparison to age, comorbidities, and performance status.